Factors Affecting the Profitability (ROA) of Businesses in the Food - Beverage Industry Listed on the Ho Chi Minh City Stock Exchange - Nguyen , Thị Thảo; Le , Thị Tú Trinh; Nguyen , Thị Kim Ngân; Tran, Thị Hoài Ly (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The purpose of this study is to investigate the factors affecting the profitability of enterprises, especially enterprises in the food industry listed on the Ho Chi Minh City Stock Exchange. The study examines and evaluates the impact of the following factors: Company size, liquidity, asset structure, revenue growth, capital structure, financial leverage, GDP, inflation on profitability (ROA). The study was conducted on 23 enterprises in the period from 2018-2023. The study uses quantitative methods: Descriptive statistics, model selection by estimating the pooled regression model (Pooled OLS), the fixed effects model (Fixed Effects Model - FEM) and the random effects model (Random Effect Model - REM) using Stata 14.2 software, and at the same time, studies to overcome defects by estimating dynamic models using the two-step D-GMM method. The overall results show that company size, liquidity, asset structure, revenue growth, financial leverage, and GDP have a positive impact on ROA. Meanwhile, profitability is not affected by inflation or capital structure. From the research results, discuss and propose some management implications to improve profitability for enterprises in the Food and Beverage industry listed on the Ho Chi Minh City Stock Exchange.